“Oh, My God! My Season Is Over!” COVID-19 and Regulation of the Psychological Response in Spanish High-Performance Athletes - González-Hernández, Juan; López-Mora, Clara; Yüce, Arif; Nogueira-López, Abel; Tovar-Gálvez, Maria Isabel (Frontiers in Psychology, 2021)
Background. In an unprecedented situation of interruption of the sporting dynamics, the world of sport is going through a series of adaptations necessary to continue functioning despite the COVID-19. More than ever, athletes are facing a different challenge, a source of discomfort and uncertainty, and one that absolutely alters not only sports calendars, but also trajectories, progressions and approaches to sports life. Therefore, it is necessary to identify the levels of psychological vulnerability that may have been generated in the athletes, due to the coexistence with dysfunctional responses during the COVID-19 experience, and which directly influence the decrease of their mental health. Methodology. With a descriptive and transversal design, the study aims to identify the state of the dysfunctional psychological response of a sample of Spanish athletes (N = 284). The DASS-21 (anxiety, stress and depression), Toronto-20 (alexithymia) and Distress Tolerance Scale questionnaires were administered to a sample of high-level Spanish athletes in Olympic programmes. Results. The results suggest that the analysed athletes indicate high levels of dysfunctional response (e.g. anxiety, stress, depression and alexithymia) when their tolerance is low. In addition, the variables show less relational strength, when the capacity of tolerance to distress is worse and age is lower. At the same time, indicators of alexithymia are worse the greater the anxiety and uncertainty, which leads to even more catastrophic and negative thoughts, the younger the athletes. Conclusions. It is clear that both age and tolerance to distress are considered adequate protective factors for psychological vulnerability in general and for associated dysfunctional responses in particular. Moreover, the psychological resources offered by more experienced athletes are also a guarantee of protection against negativity and catastrophism.